Penggunaan Aizuchi Ditinjau dari Jenis Kelamin pada Mahasiswa Bahasa Jepang Tingkat II dan III Program Studi Sastra Jepang Universitas Hasanuddin (Universitas Negeri Jakarta, 2014)
Aizuchi could be a sign whether the communication process has been working effectively or not. This research chooses qualitative method to identify the differences between both female and male of Japanese department students and Japanese native speaker’s practical custom in using aizuchi. As a result, both samples shows that female tend to use aizuchi more often than male, and Japanese native speakers use aizuchi more often than Japanese department students.As a listener, female Japanese native speakers gave response actively and tend to show their support.